2018
DOI: 10.1021/acs.organomet.8b00399
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-Heterocycle Substituted Silyl Ligands within the Coordination Sphere of Iron

Abstract: N-Heterocycle-substituted silyl iron complexes have been synthesized by nucleophilic substitution at trichlorosilyl ligands bound to iron. The homoleptic (tripyrrolyl)- and tris(3-methylindolyl)silyl groups were accessed from (Cl3Si)CpFe(CO)2 (Cl3SiFp) by substitution of chloride with pyrrolide or 3-methylindolide, respectively. Analogously, nucleophilic substitution of Cl with pyrrolide on the anionic Fe(0) synthon Cl3SiFe(CO)4– generates the (tripyrrolyl)silyl ligand, bound to the iron tetracarbonyl fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 119 publications
(213 reference statements)
0
2
0
Order By: Relevance
“…The first example of an iron silyl compound was synthesized by Wilkinson in 1956, employing the CpFe­(CO) 2 fragment . Unfortunately this compound and many other reported examples of iron silyl species to date feature coordinatively and electronically saturated metal centers, mitigating their usefulness in subsequent chemistry. Silyls have also been employed in the construction of supporting ligands, although in this capacity they are not primed for reactivity with incoming substrates. Consequently, there are relatively few examples of the synthesis and application of iron silyl compounds as hydrosilylation catalysts. ,, Further convoluting the role of silyl species in catalysis is the fact that they are often generated by oxidative addition of a Si–H bond to a reduced metal center.…”
Section: Introductionmentioning
confidence: 99%
“…The first example of an iron silyl compound was synthesized by Wilkinson in 1956, employing the CpFe­(CO) 2 fragment . Unfortunately this compound and many other reported examples of iron silyl species to date feature coordinatively and electronically saturated metal centers, mitigating their usefulness in subsequent chemistry. Silyls have also been employed in the construction of supporting ligands, although in this capacity they are not primed for reactivity with incoming substrates. Consequently, there are relatively few examples of the synthesis and application of iron silyl compounds as hydrosilylation catalysts. ,, Further convoluting the role of silyl species in catalysis is the fact that they are often generated by oxidative addition of a Si–H bond to a reduced metal center.…”
Section: Introductionmentioning
confidence: 99%
“…This distortion is also observed in complexes of iPr (P In ) 2 Si, 12 potentially due to the greater electronegativity of nitrogen than carbon as described by Bent's rule, 23 and in other silyl pyrrole complexes. 24 Notably, the dihedral angle defined by C–X–X–C (X = ipso C or N) deviates by less than a degree between the 1,2-phenylene and pyrrole-based systems; however, in the isopropyl indole-based system it is larger (14.2(2)°), potentially due to eclipsing interactions between the C7 hydrogens of the indoles. In comparing the palladium complexes, we found that the steric bulk, as determined by buried volume calculations, 25 differs by less than 1% between Ph (P Py ) 2 Si ( 4 ) and Ph (P Ph ) 2 Si.…”
Section: Resultsmentioning
confidence: 99%